Method for purifying glycolide, glycolide and application

CN117903105BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211247973.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-12
Publication Date
2026-10-30
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

但该方法存在熔体在有机溶剂中溶解与冷却结晶竞争的问题,造成晶体析出位置、析出时刻不确定等问题,从而造成析出晶体粒径不均匀、萃取效率低等问题

Benefits of technology

[0058]与现有技术通常将乙交酯直接加入到萃取溶剂中不同,本发明在萃取溶剂中加入一定量乙交酯晶体的固体颗粒,固体颗粒成为粗乙交酯熔体冷却结晶的位点,从而避免结晶位点大规模发生在器壁、搅拌桨等不理想的位点,获得粒径均匀的纯化乙交酯晶体。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a purification method of glycolide, glycolide and application. The purification method comprises the following steps: (1) adding the crude glycolide in a molten state into a solid-liquid mixture I to obtain a solid-liquid mixture II; (2) performing solid-liquid separation on the solid-liquid mixture II, and obtaining the purified glycolide after recovering the solid phase; and optionally, (3) drying the solid phase recovered in the step (2). In the application, a certain amount of solid particles is added into an extraction solvent, the solid particles become the crystallization sites of the crude glycolide melt, so that the crystallization sites are prevented from massively occurring at the undesirable sites such as the wall of a device and a stirring paddle, and the purified glycolide crystals with uniform particle size are obtained. The particle size of the purified glycolide is uniform, and the acid content is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glycolide, and more specifically, to a method for purifying glycolide, glycolide, and its applications. Background Technology

[0002] Glycolide is a compound with a cyclic dimer structure formed by removing two water molecules from two molecules of glycolic acid. Glycolide is not only a monomer for synthesizing polyglycolic acid, but it can also be copolymerized with other cyclic monomers to obtain random copolymers or block copolymers. Typically, the synthesis of glycolide monomer involves two steps: first, the condensation polymerization of glycolic acid to form a low molecular weight polymer, called glycolic acid oligomer; second, the glycolic acid oligomer is depolymerized by high-temperature distillation to extract the gaseous product glycolide from the reaction system.

[0003] The glycolide obtained from the above reaction typically contains various impurities such as water, glycolic acid, and glycolic acid oligomers, and is therefore called crude glycolide. The trace amounts of active hydrogen contained in these impurities can significantly affect the molecular weight of the polymer during the ring-opening polymerization of glycolide, failing to meet the requirements of polyglycolic acid for applications such as surgical sutures, which demands an intrinsic viscosity of not less than 1 and a mass-average molecular weight of not less than 100,000. Therefore, crude glycolide obtained through depolymerization needs to be purified through recrystallization or washing, a process referred to in this patent as refining.

[0004] Reported purification methods employ various organic solvents and involve multiple recrystallizations. For example, Example 3 of US Patent 4727163A uses ethyl acetate to purify crude glycolide obtained from the depolymerization of glycolic acid oligomers. Two recrystallizations only achieve a 59.4% yield, reducing the crude glycolide purity to 90%. To obtain higher purity glycolide, more recrystallization cycles are required, resulting in higher solvent consumption, large amounts of waste liquid to be treated, and the presence of various impurities from the crude glycolide. Furthermore, recrystallization operations are typically complex; therefore, many researchers are exploring new methods for purifying glycolide.

[0005] Existing technologies also include purification methods involving multiple alcohol washings. Chinese invention patent CN107868075A discloses a purification method for glycolide, which purifies crude glycolide by employing a method of cooling recrystallization and washing with a poor solvent followed by filtration and drying. This method uses alcohols as washing solvents, and the solubility of alcohols in glycolide is significantly lower than that of good solvents such as ethyl acetate, which increases the yield of single-pass purification. However, the amount of solvent used in the purification process is still very large, and the problem of high difficulty in solvent recycling also exists.

[0006] Japanese Invention Patent JP1984148777A discloses a method for purifying crude lactide by receiving crude lactide melt with ethyl acetate at low temperature. This method avoids the thermal degradation of crude lactide and obtains high-purity lactide in a high yield. At a lower temperature, crude lactide is melted by heating and added dropwise to an organic solvent under stirring. The resulting lactide suspension is then cooled to a specific temperature, and the precipitate is separated and dried. However, this method suffers from competition between the dissolution of the melt in the organic solvent and the cooling crystallization, resulting in uncertain crystal precipitation locations and times, leading to uneven crystal particle size and low extraction efficiency. Summary of the Invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides a method for purifying glycolide, glycolide, and its applications.

[0008] In this invention, crude glycolide melt is added to a solid-liquid mixture I at a certain rate, while simultaneously completing the cooling crystallization and extraction processes. That is, solid particles are rapidly and uniformly precipitated, and impurities are extracted into the liquid phase to generate purified glycolide crystals. The purified glycolide crystals can then be recovered through a solid-liquid separation process.

[0009] This invention solves several problems existing in the prior art by adding a certain amount of solid particles to a pure organic solvent and using a solid-liquid mixture to receive the glycolide melt. Compared with the traditional recrystallization process, the process temperature is constant and there is no cooling process with a large temperature range. It has the advantages of simple operation, easy industrial scale-up, and low energy consumption.

[0010] Existing technologies address the high acid content problem by increasing the amount of organic solvent and the number of refining stages, resulting in high solvent consumption, long refining processes, and cumbersome operations. Purification methods that do not use organic solvents, such as melt crystallization and distillation, also address high acid content by increasing the number of refining stages, similarly suffering from long refining processes and cumbersome operations. This invention not only solves the technical problem of high acid content in glycolide but also addresses the issue of uneven crystal particle size during crystallization, providing a simple and efficient method for refining glycolide, resulting in purified glycolide with uniform particle size and low acid content.

[0011] One objective of this invention is to provide a method for purifying glycolide, comprising the following steps:

[0012] (1) Molten crude glycolide is added to solid-liquid mixture I to obtain solid-liquid mixture II; the solid-liquid mixture I contains glycolide crystals and glycolide solution;

[0013] (2) The solid-liquid mixture II was separated into solid and liquid phases, and the purified glycolide was obtained after recovering the solid phase;

[0014] Optionally, (3) the solid phase recovered in step (2) is dried.

[0015] In a preferred embodiment of the present invention,

[0016] Step (1),

[0017] The addition method is at least one of dripping, injecting, spraying, sprinkling, or misting; and / or,

[0018] The molten crude glycolide is unrefined molten crude glycolide and / or refined molten crude glycolide; and / or,

[0019] The molten crude glycolide contains 85% to 99% glycolide by mass.

[0020] In a preferred embodiment of the present invention,

[0021] The unpurified molten crude glycolide is obtained by pyrolysis and cyclization reaction of glycolic acid oligomers; preferably, it is obtained by condensation of the gaseous product generated by the pyrolysis and cyclization reaction of glycolic acid oligomers, or by deep condensation of the gaseous product to obtain solid crude glycolide, and then heating and melting it.

[0022] The purified molten crude glycolide is a molten substance containing the glycolide phase obtained by purifying crude glycolide obtained from glycolic acid oligomers through a cyclopyrolysis reaction using conventional methods. After conventional purification, the crude glycolide should be processed into a molten state before further purification using the method of this invention. If the material containing the glycolide phase after conventional purification is in a gaseous phase, the gaseous phase is condensed into a molten state. If the material containing the glycolide phase after conventional purification is in a solid phase, it is heated and melted into a molten state.

[0023] The conventional purification method described above is a conventional purification method in the prior art for crude glycolide obtained by cleavage and cyclization reaction of glycolic acid oligomers, including the steps of extraction, washing, crystallization and distillation of the unpurified crude glycolide.

[0024] In a preferred embodiment of the present invention,

[0025] The temperature of the unpurified molten crude glycolide is 75℃~120℃; preferably 80℃~95℃; and / or,

[0026] The temperature of the purified molten crude glycolide is 80℃~120℃; preferably 85℃~95℃.

[0027] Unrefined crude glycolide has a lower melting point. If it is a mixture of unrefined molten crude glycolide and refined molten crude glycolide, the melting point will be higher. Therefore, its temperature range in the molten state will be correspondingly higher, and will be consistent with the temperature range of refined molten crude glycolide.

[0028] In a preferred embodiment of the present invention,

[0029] Step (1),

[0030] Add 20wt% to 500wt% of molten crude glycolide, preferably 50wt% to 200wt%, of the solid-liquid mixture I per hour; the addition rate is expressed as the proportion of the mass added per unit time to the mass of the solid-liquid mixture I.

[0031] The temperatures of both solid-liquid mixture I and solid-liquid mixture II shall not exceed 60°C; preferably, they shall not exceed 50°C. Since glycolide has thermal degradation characteristics, solid-liquid mixture I needs to be kept below 60°C before it is added.

[0032] When crude glycolide melt is added to solid-liquid mixture I at a certain rate, the addition process raises the temperature of the solid-liquid mixture due to the higher temperature of the melt itself and the exothermic cooling and crystallization. To maintain a stable temperature in the solid-liquid mixture, the addition rate needs to be matched with the heat exchange (cooling) power to ensure a stable crystallization-extraction process. The temperature of the solid-liquid mixture must be kept within the preferred temperature range for two reasons: to avoid thermal degradation of glycolide and to provide a sufficient temperature difference for the glycolide melt to cool and crystallize. The glycolic acid and glycolic acid oligomers (glycolic acid dimers, etc.) contained in crude glycolide can provide the necessary alcohol hydroxyl groups (initiators) and protic acids (catalysts) for the ring-opening polymerization of glycolide. At a certain temperature, for example, greater than or equal to 60°C, the ring-opening polymerization reaction can occur significantly, generating glycolic acid oligomers with higher molecular weight (degree of polymerization greater than or equal to 7). The ring-opening polymerization side reaction that occurs during the purification process is a typical thermal degradation. Its reaction degree is affected by the concentration of initiator and catalyst, as well as temperature and time. The oligomers generated are usually difficult to remove because they have low solubility in common organic solvents.

[0033] In a preferred embodiment of the present invention,

[0034] Step (1),

[0035] The solid phase of solid-liquid mixture I is glycolide crystals with a purity higher than 95%; preferably, glycolide crystals with a purity higher than 99%; and / or,

[0036] The liquid phase of the solid-liquid mixture I is a saturated solution of glycolide in an organic solvent; the organic solvent is a good solvent for glycolide, preferably at least one of acetone, ethyl acetate, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, and isopentanol. These organic solvents have high solubility for impurities such as pigments and acids in crude glycolide.

[0037] In a preferred embodiment of the present invention,

[0038] Step (1),

[0039] The mass fraction of the solid phase in the solid-liquid mixture I is 0.5% to 25%; preferably 2% to 25%.

[0040] A solid phase mass fraction of ≥0.5% in solid-liquid mixture I can provide sufficient crystallization sites for the molten cooling and crystallization of crude glycolide.

[0041] The mass fraction of the solid phase in solid-liquid mixture II is less than or equal to 50%; preferably less than or equal to 40%.

[0042] In a preferred embodiment of the present invention,

[0043] Step (1),

[0044] The median diameter of the solid phase in the solid-liquid mixture I is less than or equal to 200 micrometers; preferably less than or equal to 150 micrometers.

[0045] The median diameter of the solid phase in the solid-liquid mixture II is less than or equal to 600 micrometers; preferably less than or equal to 500 micrometers.

[0046] The solid phase particles of solid-liquid mixture I are smaller in size, which is beneficial for stirring and dispersion, and for obtaining a uniform solid-liquid mixture;

[0047] The solid particle size of the solid-liquid mixture I is controlled by conventional methods in the prior art. For example, the crystal particles can be pre-processed into the required particle size by physical crushing and sieving, and then added to the saturated solution to form a mixture. During mixing, a stirring system with dispersion function is preferred. In the production equipment, the stirring speed is preferably not more than 200 rpm.

[0048] The following inferences drawn by the inventors are not bound by any existing theories: Particles in solid-liquid mixture I, under a preferred particle size, can be uniformly suspended in the solid-liquid mixture under the agitation of conventional stirring paddles such as folding paddles or spiral paddles, becoming sites for the cooling and crystallization of crude glycolide melt. This avoids large-scale crystallization sites occurring on undesirable sites such as the vessel wall and stirring paddle, resulting in purified glycolide crystals with uniform particle size. With the same solid phase mass fraction in solid-liquid mixture I, smaller solid phase particle size results in a greater number of particles in the solid-liquid mixture, providing more crystallization sites and benefiting the uniformity of crystallization. When the glycolide phase in the crude glycolide melt contacts the particles in solid-liquid mixture I, it continues to grow on its surface, further increasing the crystal particle size in solid-liquid mixture II. To ensure the efficiency of the extraction process and allow impurities such as pigments and acids to fully diffuse into the organic solvent (e.g., more than 80% of the acid is extracted into the organic solvent), the particle size of glycolide crystals in solid-liquid mixture II should be as small as possible.

[0049] In a preferred embodiment of the present invention,

[0050] Step (2), the solid-liquid separation method is centrifugation or filtration;

[0051] Step (3) The solid-phase drying method is convection drying under a hot inert gas or thermal conduction drying under vacuum.

[0052] In a preferred embodiment of the present invention,

[0053] Repeat steps (1) and (2) and optionally (3) at least once to obtain further purified glycolide crystals.

[0054] A second objective of this invention is to provide a glycolide obtained by the above purification method.

[0055] A third objective of this invention is to provide an application of glycolide in the preparation of polyglycolic acid.

[0056] The purified glycolide crystals obtained by this invention can be used as monomers for the polymerization of polyglycolic acid.

[0057] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0058] Unlike existing technologies that typically add glycolide directly to the extraction solvent, this invention adds a certain amount of glycolide crystal solid particles to the extraction solvent. These solid particles become sites for the cooling and crystallization of the crude glycolide melt, thereby avoiding large-scale crystallization sites occurring on undesirable sites such as the vessel wall and stirring paddle, and obtaining purified glycolide crystals with uniform particle size.

[0059] The solid-phase glycolide crystals added in this invention have a very small average particle size, resulting in smaller average particle size of the newly formed crystals. This facilitates the full diffusion of impurities such as pigments and acids into the organic solvent, leading to higher extraction efficiency and lower acid content in the glycolide. Compared with the method of directly adding glycolide melt to the extraction solvent, the glycolide has a lower acid content with the same amount of organic solvent. Acidic impurities are the main impurities in crude glycolide. After being fully removed, it can be used for ring-opening polymerization, and the purified glycolide has a high purity.

[0060] This invention uses a solid-liquid mixture to receive the glycolide melt. Compared with the traditional recrystallization process, the process temperature is constant and there is no cooling process with a large temperature range. It has the advantages of simple operation, easy industrial scale-up, and low energy consumption. Detailed Implementation

[0061] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0062] All raw materials used in the examples are commercially available.

[0063] The method for testing the average particle size of lactide crystals in this invention is as follows:

[0064] The average particle size (median diameter, i.e., the particle size at which the cumulative volume distribution of particles is 50%), D10 particle size (the volume content of particles smaller than this size accounts for 10% of all particles), and D90 particle size (the volume content of particles smaller than this size accounts for 90% of all particles) of glycolide were determined using a Malvern Mastersizer 3000 laser particle size analyzer. The smaller the ratio of D90 to D10, the narrower the particle size distribution. Isopropanol was used as the dispersion medium.

[0065] The method for determining the free acid concentration of crude glycolide and glycolide in this invention is as follows:

[0066] The concentration of free acid in crude glycolide was determined using an acid-base titration method. The specific procedure is as follows: The crude glycolide sample was dissolved in approximately 30 mL of dry dimethyl sulfoxide. After dissolution, a few drops of bromophenol blue indicator solution were added, resulting in a yellow solution. Titration was then performed using a dilute solution of sodium hydroxide in benzyl alcohol of known concentration. The endpoint was reached when the solution color changed from yellow to green. The terminal carboxyl group content (in μmol) in the glycolide was calculated by calculating the volume of sodium hydroxide solution used to reach the titration endpoint. Dividing this volume by the mass of the crude glycolide sample yielded the free acid concentration (in μmol / g).

[0067] The method for determining the purity of glycolide in this invention is as follows:

[0068] The purity of glycolide was determined by gas chromatography (GC). 200 mg of the glycolide sample and 40 mg of p-chlorobenzophenone (internal standard) were dissolved in 10 mL of acetone. 2 μL of the solution was injected into the gas chromatograph to determine the glycolide content. The glycolide purity was determined using a standard calibration curve prepared beforehand with glycolide standards (at least 5 spots between 160 and 200 mg) and the internal standard (40 mg p-chlorobenzophenone). The apparatus used was an Agilent 7890B, with an HP-5 capillary column (30 m × 0.32 mm, 0.25 μm), a column temperature of 280 °C, an injection port temperature of 150 °C, and an FID detector.

[0069]

Example 1

[0070] Preparation of crude glycolide:

[0071] After adding 600g of glycolic acid crystals and 6g of stannous octoate catalyst to the reactor, the temperature was raised from room temperature to 90℃. After the solid was completely dissolved, the temperature was raised to 120℃ to start atmospheric pressure prepolymerization. After 2 hours of prepolymerization, the temperature was raised to 210℃. After the anhydrous distillation, the system temperature was maintained and a vacuum was started. The vacuum degree was controlled at 2kPa during this process. After the anhydrous distillation, 475g of glycolic acid oligomer was obtained.

[0072] The oligomer was fed into a depolymerization reactor. The depolymerization system was reacted at a reaction temperature of 285℃, a vacuum of 3kPa, and a stirring speed of 120rpm to prepare crude glycolide. The crude glycolide vapor produced by the depolymerization reactor was condensed using a spherical condenser with a jacket water temperature of 85℃ to obtain molten crude glycolide. The reaction was stopped after 2 hours, yielding 395g of crude glycolide with an acid content of 450μmol / g and a glycolide purity of 90.20%.

[0073] Purification of glycolide:

[0074] 250g of the above crude glycolide melt was kept at 90°C in jacketed reactor A. 600g of a mixture of ethyl acetate and glycolide was added to jacketed reactor B, with 100g of solid glycolide (median diameter 103 μm, acid content 1.7 μmol / g, GC purity 99.86%) suspended in the mixture. The mixture was stirred at 120 rpm and kept at 10°C. The melt from reactor A was added dropwise to reactor B at a rate of 70 wt% of the solid-liquid mixture per hour, with stirring at 120 rpm and the internal temperature maintained at 12°C. After completion, a solid-liquid mixture with a solid content of 35.3 wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 275 μm, and the D90 to D10 ratio was 3.9. The purified glycolide crystals were obtained by vacuum drying at 60°C for 4 hours, with an acid content of 45 μmol / g and a GC purity of 98.0%.

[0075]

Example 2

[0076] The preparation of crude glycolide is the same as in Example 1.

[0077] Purification of glycolide:

[0078] 250g of the above crude glycolide melt was kept at 90°C in jacketed reactor A. 530g of a mixture of isopropanol and glycolide was added to jacketed reactor B, with 30g of glycolide solid suspended in the mixture (median diameter 103 μm, acid content 1.7 μmol / g, GC purity 99.86%). The mixture was stirred at 120 rpm and kept at 35°C. The melt from reactor A was added dropwise to reactor B at a rate of 70 wt% of the solid-liquid mixture per hour, with stirring at 120 rpm and the internal temperature maintained at 36°C. After completion, a solid-liquid mixture with a solid content of 31.7 wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 300 μm, and the D90 to D10 ratio was 4.3. The purified glycolide crystals were obtained by vacuum drying at 60°C for 4 hours, with an acid content of 42 μmol / g and a GC purity of 98.2%.

[0079]

Example 3

[0080] The preparation of crude glycolide is the same as in Example 1.

[0081] Purification of glycolide:

[0082] 250g of the above crude glycolide melt was kept at 90°C in jacketed reactor A. 515g of a mixture of isopropanol and glycolide was added to jacketed reactor B, with 15g of glycolide solid suspended in the mixture (median diameter 103 μm, acid content 1.7 μmol / g, GC purity 99.86%). The mixture was stirred at 120 rpm and kept at 35°C. The melt from reactor A was added dropwise to reactor B at a rate of 70 wt% of the solid-liquid mixture per hour, with stirring at 120 rpm and the internal temperature maintained at 36°C. After completion, a solid-liquid mixture with a solid content of 30.4 wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 500 μm, and the D90 to D10 ratio was 4.7. The purified glycolide crystals were obtained by vacuum drying at 60°C for 4 hours, with an acid content of 75 μmol / g and a GC purity of 97.1%.

[0083]

Example 4

[0084] The preparation of crude glycolide is the same as in Example 1.

[0085] Purification of glycolide:

[0086] 250g of the above crude glycolide melt was kept at 90°C in jacketed reactor A. 450g of a mixture of ethanol and glycolide was added to jacketed reactor B, with 75g of glycolide solid suspended in the mixture (median diameter 103 μm, acid content 1.7 μmol / g, GC purity 99.86%). The mixture was stirred at 120 rpm and kept at 45°C. The melt from reactor A was added dropwise to reactor B at a rate of 70 wt% of the solid-liquid mixture per hour, with stirring at 120 rpm and the internal temperature maintained at 48°C. After completion, a solid-liquid mixture with a solid content of 40.0 wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 268 μm, and the D90 to D10 ratio was 5.2. The purified glycolide crystals were obtained by vacuum drying at 60°C for 4 hours, with an acid content of 73 μmol / g and a GC purity of 97.5%.

[0087]

Example 5

[0088] The purified glycolide crystals (GC purity 98.0%) obtained in Example 1 were subjected to a second purification.

[0089] Secondary purification of glycolide:

[0090] 150g of purified glycolide crystals were heated and melted. The melt was kept at 90°C in jacketed reactor A. 360g of a mixture of ethyl acetate and glycolide was added to jacketed reactor B, in which 60g of glycolide solid (median diameter 103 μm, acid content 1.7 μmol / g, GC purity 99.86%) was suspended. The mixture was stirred at 120 rpm and kept at 10°C. The melt in reactor A was added dropwise to reactor B at a rate of 70 wt% of the solid-liquid mixture per hour, while the stirring rate was 120 rpm and the internal temperature was maintained at 12 °C. After completion, a solid-liquid mixture with a solid content of 37.6 wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 295 μm, and the D90 to D10 ratio was 3.6. The purified glycolide crystals were obtained by vacuum drying at 60 °C for 4 h, with an acid content of 2.8 μmol / g and a purity of 99.6% as determined by GC.

[0091]

Example 6

[0092] The purified glycolide crystals (GC purity 98.2%) obtained in Example 2 were subjected to a second purification.

[0093] Secondary purification of glycolide:

[0094] 150g of purified glycolide crystals were heated and melted. The melt was kept at 90°C in jacketed reactor A. 318g of a mixture of isopropanol and glycolide was added to jacketed reactor B, in which 18g of glycolide solid (median diameter 103 μm, acid content 1.7 μmol / g, GC purity 99.86%) was suspended. The mixture was stirred at 120 rpm and kept at 35°C. The melt in reactor A was added dropwise to reactor B at a rate of 70 wt% of the solid-liquid mixture per hour, while the stirring rate was 120 rpm and the internal temperature was maintained at 36 °C. After completion, a solid-liquid mixture with a solid content of 34.6 wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 340 μm, and the D90 to D10 ratio was 4.0. The purified glycolide crystals were obtained by vacuum drying at 60 °C for 4 h, with an acid content of 3.2 μmol / g and a purity of 99.5% as determined by GC.

[0095]

Example 7

[0096] Preparation of crude glycolide:

[0097] The difference from Example 1 is that the depolymerization system was carried out at a reaction temperature of 255°C. The crude glycolate vapor produced in the depolymerization reactor was condensed using a spherical condenser with a jacketed water temperature of 7°C to obtain solid crude glycolate. The reaction was stopped after 4 hours. 372g of crude glycolate was obtained, with an acid content of 570μmol / g and a glycolate purity of 86.0%.

[0098] Apart from the differences mentioned above, everything else is the same as in Example 1.

[0099] Purification of glycolide:

[0100] 250g of crude glycolide solid was heated and melted. The melt was kept at 93°C in jacketed reactor A. 600g of a mixture of ethyl acetate and glycolide was added to jacketed reactor B, in which 100g of glycolide solid (median diameter 145 μm, acid content 6.0 μmol / g, GC purity 99.30%) was suspended. The mixture was stirred at 120 rpm and kept at 10°C. The melt in reactor A was added dropwise to reactor B at a rate of 50 wt% of the solid-liquid mixture per hour, while the stirring rate was 120 rpm and the internal temperature was maintained at 12 °C. After completion, a solid-liquid mixture with a solid content of 32.5 wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 293 μm, and the D90 to D10 ratio was 3.8. The purified glycolide crystals were obtained by vacuum drying at 60 °C for 4 h, with an acid content of 72 μmol / g and a purity of 96.8% as determined by GC.

[0101]

Example 8

[0102] The preparation of crude glycolide was the same as in Example 7.

[0103] Purification of glycolide:

[0104] The only difference from Example 7 is that the melt in reactor A was added dropwise to reactor B at a rate of 190 wt% of the solid-liquid mixture per hour; after completion, a solid-liquid mixture with a solid content of 33.0 wt% was obtained, the median diameter of the glycolide crystals in the filter cake was 318 μm, the ratio of D90 to D10 was 4.5, the acid content of the purified glycolide crystals was 77 μmol / g, and the purity measured by GC was 96.5%.

[0105] Apart from the differences mentioned above, everything else is the same as in Example 7.

[0106]

Example 9

[0107] The preparation of crude glycolide was the same as in Example 7.

[0108] Purification of glycolide:

[0109] The only difference from Example 7 is that the melt in reactor A was added dropwise to reactor B at a rate of 120 wt% of the solid-liquid mixture per hour; after completion, a solid-liquid mixture with a solid content of 32.9 wt% was obtained, the median diameter of the glycolide crystals in the filter cake was 305 μm, the ratio of D90 to D10 was 4.2, the acid content of the purified glycolide crystals was 76 μmol / g, and the purity measured by GC was 96.6%;

[0110] Apart from the differences mentioned above, everything else is the same as in Example 7.

[0111]

Example 10

[0112] The preparation of crude glycolide was the same as in Example 7.

[0113] Purification of glycolide:

[0114] The only difference from Example 7 is that 250g of crude glycolide solid was heated and melted, and the melt was kept at 80°C in a jacketed reactor A. After completion, a solid-liquid mixture with a solid content of 32.8wt% was obtained. The median diameter of glycolide crystals in the filter cake was 290μm, the ratio of D90 to D10 was 5.0, the acid content of the purified glycolide crystals was 70μmol / g, and the purity measured by GC was 96.8%.

[0115] Apart from the differences mentioned above, everything else is the same as in Example 7.

[0116]

Example 11

[0117] The preparation of crude glycolide was the same as in Example 7.

[0118] Purification of glycolide:

[0119] The only difference from Example 7 was that 600 g of a mixture of ethyl acetate and glycolide was added to jacketed reactor B, wherein 140 g of glycolide solid was suspended in the mixture; after completion, a solid-liquid mixture with a solid content of 37.6 wt% was obtained, the median diameter of glycolide crystals in the filter cake was 279 μm, the D90 to D10 ratio was 3.7, the acid content of the purified glycolide crystals was 68 μmol / g, and the purity measured by GC was 96.8%;

[0120] Apart from the differences mentioned above, everything else is the same as in Example 7.

[0121]

Example 12

[0122] The difference from Example 7 lies in the crude glycolide;

[0123] The crude glycolide used in this invention is glycolide prepared according to the method described in Example 1 of the invention patent CN107868075A (conventional purification method), with an acid content of 12.0 μmol / g and a glycolide GC purity of 98.9%.

[0124] Except for the differences mentioned above, all other purification steps are the same as in Example 7;

[0125] After purification, glycolide was obtained as a solid-liquid mixture with a solid content of 35.3 wt%. The median diameter of glycolide crystals in the filter cake was 311 μm, the ratio of D90 to D10 was 3.7, the acid content of the purified glycolide crystals was 0.80 μmol / g, and the purity measured by GC was 99.7%.

[0126] Comparative Example 1

[0127] Preparation of crude glycolide:

[0128] The preparation of crude glycolide was the same as in Example 1, with an acid content of 450 μmol / g and a glycolide purity of 90.20%.

[0129] Purification of glycolide:

[0130] 250g of the above crude glycolide melt was kept at 90℃ in jacketed reactor A. 500g of ethyl acetate was added to jacketed reactor B, and the mixture was stirred at 120rpm and kept at 10℃. The melt in reactor A was transferred to reactor B at a rate of 70wt% of solvent mass per hour, with stirring at 120rpm and the internal temperature maintained at 12℃. After completion, a solid-liquid mixture with a solid content of 25.1wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 725μm, and the D90 to D10 ratio was 11.1. The purified glycolide crystals were obtained by vacuum drying at 60℃ for 4h, with an acid content of 123μmol / g and a purity of 96.5% as determined by GC.

[0131] Comparative Example 2

[0132] The purified glycolide crystals (GC purity 96.5%) obtained in Comparative Example 1 were subjected to a second purification.

[0133] Secondary purification of glycolide:

[0134] 150g of purified glycolide crystals were melted by heating. The melt was kept at 90°C in jacketed reactor A. 300g of ethyl acetate was added to jacketed reactor B, and the mixture was stirred at 120rpm and kept at 10°C. The melt in reactor A was transferred to reactor B by adding solvent at a rate of 70wt% per hour, while the stirring rate was maintained at 120rpm and the internal temperature was maintained at 12°C. After completion, a solid-liquid mixture with a solid content of 26.9wt% was obtained. The filter cake was collected by vacuum filtration under nitrogen protection. The median diameter of the glycolide crystals in the filter cake was measured to be 843μm, and the D90 to D10 ratio was 8.5. The purified glycolide crystals were obtained by vacuum drying at 60°C for 4h, with an acid content of 18.1μmol / g and a purity of 98.5% as determined by GC.

[0135] Comparative Example 1 is glycolide purified by conventional methods. Compared with Comparative Example 1, the median diameter of the purified solid phase in Example 1 is 275 μm and 725 μm, respectively; the acid content is 45 μmol / g and 123 μmol / g, respectively; the D90 to D10 ratio is 3.9 and 11.1, respectively; and the GC purity is 98.0% and 96.5%, respectively.

[0136] Comparative Example 2 involved secondary purification of the glycolide obtained in Comparative Example 1 using conventional methods. Example 5 involved secondary purification of the glycolide obtained in Example 1 using the method of the present invention. Compared with Comparative Example 2, the median diameter of the purified solid phase in Example 5 was 295 μm and 843 μm, respectively; the acid content was 2.8 μmol / g and 18.1 μmol / g, respectively; the D90 to D10 ratio was 3.6 and 8.5, respectively; and the GC purity was 99.6% and 98.5%, respectively.

[0137] The data comparison above shows that, compared with conventional purification methods of the prior art, the purification method of the present invention results in a smaller median diameter of the solid phase, lower acid content, more uniform particle size distribution, and higher purity. Furthermore, the method of the present invention allows for secondary purification, and the glycolide obtained after secondary purification exhibits even better performance.

[0138] Example 12 further purified glycolide with a GC purity of 98.9% obtained by conventional purification methods. The median diameter of the obtained glycolide was 311 μm, the D90 to D10 ratio was 3.7, the acid content of the purified glycolide crystals was 0.80 μmol / g, and the purity measured by GC was 99.7%. This further proves that the present invention can purify glycolide with higher purity, reducing its acid content while achieving higher purity.

[0139] Test results show that the glycolide purified in Examples 1-12 has a small and uniform particle size, low acid content, and high purity. Furthermore, the present invention uses a solid-liquid mixture to receive the glycolide melt. Compared with the traditional recrystallization process, the process temperature is constant, there is no cooling process with a large temperature range, the operation is simple, the energy consumption is low, and it is suitable for industrialization.

Claims

1. A method for purifying glycolide, comprising the following steps: (1) Molten crude glycolide is added to solid-liquid mixture I to obtain solid-liquid mixture II; the solid-liquid mixture I contains glycolide crystals and glycolide solution; (2) The solid-liquid mixture II was separated into solid and liquid phases, and the purified glycolide was obtained after recovering the solid phase; Optionally, (3) the solid phase recovered in step (2) is dried; The molten crude glycolide is unrefined molten crude glycolide and / or refined molten crude glycolide; the temperature of the unrefined molten crude glycolide is 75℃~120℃; the temperature of the refined molten crude glycolide is 80℃~120℃; the glycolide content in the molten crude glycolide is 85%~99% by mass; the solid phase of the solid-liquid mixture I is glycolide crystals with a glycolide purity higher than 95%; the liquid phase of the solid-liquid mixture I is a saturated solution of glycolide in an organic solvent; the temperatures of both the solid-liquid mixture I and the solid-liquid mixture II do not exceed 60℃; 20wt%~500wt% of the mass of molten crude glycolide is added to the solid-liquid mixture I every hour.

2. The method for purifying glycolide as described in claim 1, characterized in that: Step (1), The addition method is at least one of dripping, injecting, spraying, sprinkling, and misting.

3. The method for purifying glycolide as described in claim 1, characterized in that: The temperature of the unpurified molten crude glycolide is 80℃~95℃; and / or, The purified molten crude glycolide was prepared at a temperature of 85°C to 95°C.

4. The method for purifying glycolide as described in claim 1, characterized in that: Step (1), Add 50wt% to 200wt% of molten crude glycolide per hour from the solid-liquid mixture I; and / or, The temperatures of both solid-liquid mixture I and solid-liquid mixture II do not exceed 50℃.

5. The method for purifying glycolide as described in claim 1, characterized in that: Step (1), The solid phase of solid-liquid mixture I is glycolide crystals with a purity higher than 99%; and / or, The organic solvent in the liquid phase of solid-liquid mixture I is at least one of acetone, ethyl acetate, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, and isopentanol.

6. The method for purifying glycolide as described in claim 1, characterized in that: Step (1), The mass fraction of the solid phase in the solid-liquid mixture I is 0.5%~25%; and / or, The mass fraction of the solid phase in solid-liquid mixture II is less than or equal to 50%.

7. The method for purifying glycolide as described in claim 6, characterized in that: Step (1), The solid-liquid mixture I has a solid phase mass fraction of 2% to 25%; and / or, The mass fraction of the solid phase in solid-liquid mixture II is less than or equal to 40%.

8. The method for purifying glycolide as described in claim 1, characterized in that: Step (1), The median diameter of the solid phase in the solid-liquid mixture I is less than or equal to 200 micrometers; and / or, The median diameter of the solid phase in the solid-liquid mixture II is less than or equal to 600 micrometers.

9. The method for purifying glycolide as described in claim 8, characterized in that: Step (1), The median diameter of the solid phase in the solid-liquid mixture I is less than or equal to 150 micrometers; and / or, The median diameter of the solid phase in the solid-liquid mixture II is less than or equal to 500 micrometers.

10. The method for purifying glycolide as described in claim 1, characterized in that: In step (2), the solid-liquid separation method is centrifugation or filtration; and / or, In step (3), the solid-phase drying method is either convection drying under a thermal inert gas or thermal conduction drying under a vacuum.

11. The method for purifying glycolide according to any one of claims 1 to 10, characterized in that: Repeat steps (1) and (2) and optionally step (3) at least once.

Citation Information

Patent Citations

  • Method for refining glycolide

    CN107868075A

  • Purification of crude glycollide

    JP1984148777A

  • Process for preparing highly pure cyclic esters

    US4727163A

  • Synthesis method of high-purity glycolide

    CN113278005A